Capital Adequacy and Financial Performance of Banks in Nigeria: Empirical Evidence Based on the Fgls Estimator - David Umoru; Joy O. Osemwegie (European Scientific Journal, ESJ, 2016)
The study examines the degree of significance of the capital adequacy ratio in influencing the financial deeds of Nigerian banks by applying the feasible GLS estimator technique on the pooled panel model for the period of 2007 to 2015. Empirical evidence supports the overriding impact of capital adequacy in enhancing the financial deeds of Nigerian banks. Nevertheless, the impact of the estimated capital adequacy is below 30%. The policy stance of the empirics holds thus that depositor’s money in the banking sector has not been absolutely assured. Hence, the deposit money banks might not be able to fulfil their liabilities and risk. In light of the findings, we suggested a constant reassessment of the least amount of capital required of banks by the CBN.